ЗНАХІДКА РІДКІСНОГО ДЛЯ ЧОРНОГО МОРЯ ВИДУ КРЕВЕТКИ ALPHEUS DENTIPES GUERIN, 1832 (DECAPODA: ALPHEIDAE) В ПРИБЕРЕЖЖІ ПІВДЕННО-ЗАХІДНОГО КРИМУ - Статкевич, С. В.; Турбанов, И. С. (Marine Ecological Journal, 2023)
The finding of the rare shrimp Alpheus dentipes Guerin, 1832 (Decapoda: Alpheidae) in the coastal waters of the south-western Crimea.